The unique value and controversy of nuclear medicine molecular imaging in the evaluation of radioiodine-refractory differentiated thyroid cancer - WANG Renfei, LU Gaixia (Zhongguo aizheng zazhi)
Nuclear medicine molecular imaging has the characteristics of non-invasiveness, high sensitivity, spatiotemporal dynamic visualization, qualitative and quantitative analysis, and by virtue of the advantages of fusion imaging technology, it combines the features of functional metabolism and anatomical structure. Nuclear medicine molecular imaging evaluation is integrated throughout the management of radioactive iodine-refractory differentiated thyroid cancer (RAIR-DTC), including defining RAIR, exploring the lesions, guiding treatment decisions, evaluating efficacy, and assessing prognosis. 131I-whole body scan (131I-WBS) is critical for determining RAIR-DTC. Diagnostic 131I-WBS can be used to explore postoperative residual thyroid and suspected iodine-avid metastases before 131I treatment, which is helpful for subsequent 131I treatment decisions. Post-treatment 131I-WBS can further clarify the iodine uptake characteristics of lesions and explore lesions not shown by diagnostic WBS, providing a reference for clarifying the clinical stage of patients and formulating follow-up management plans. The iodine uptake ability of lesions shown by post-treatment 131I-WBS can also predict the therapeutic efficacy of 131I treatment. 131I-WBS combined with biochemical changes and other imaging examinations can also be used to evaluate the therapeutic efficacy of 131I treatment. 18F-FDG positron emission tomography and computed tomography (PET/CT) is mainly used for high-risk DTC patients with persistently elevated serum thyroglobulin (Tg) or Tg antibody (TgAb) levels and negative 131I-WBS, and can explore and locate lesions. Combining 18F-FDG PET/CT with 131I-WBS provides a thorough evaluation of the overall tumor burden. The uptake of 18F-FDG by DTC metastases indicates poor 131I treatment response and poor prognosis for patients, and is a predictor of rapid disease progression and an increased risk of tumor-specific death. After local or systemic treatment of RAIR-DTC lesions, the early metabolic response to treatment can predict the clinical benefit of patients, allowing for timely adjustment of treatment strategies. In addition, various new radionuclide imaging techniques targeting angiogenesis (such as RGD peptides and prostate specific membrane antigen), fibroblast activation protein and somatostatin receptor can be used as supplementary means when 18F-FDG PET/CT is negative to detect RAIR-DTC lesions. They can also screen patients who qualify for targeted radionuclide therapy based on the uptake ability of imaging agents. These novel theranostics provide new options for progressive RAIR-DTC patients after multiline treatment.